Adjusting the band structure and defects of ZnO quantum dots via tin doping. Issue 19 (14th February 2017) - Yang, Weimin; Zhang, Bing; Zhang, Qitu; Wang, Lixi; Song, Bo; Ding, Yong; Wong, C. P.
Abstract : The structures and band structures of Sn doped ZnO were investigated by density functional theory as well as experiment. Abstract : The structures and band structures of Sn doped ZnO were investigated by density functional theory (DFT). Sn-doped ZnO quantum dots were also synthesized via an ultrasonic sol–gel method. The charge of Sn ions was also taken into consideration and Sn 2+ and Sn 4+ were employed. UV-Vis absorption spectra and photoluminescence excitation spectra were used to elucidate the band gap of Sn-doped ZnO QDs. Photoluminescence spectra were employed to study the change in the defects of Sn-doped ZnO QDs. Sn doping reduced the symmetry of the ZnO cell and stretched the cell. Furthermore, it also could change ZnO from a direct gap semiconductor to an indirect gap semiconductor. The experimental results and DFT calculations matched quite well. Both the DFT calculations and experimental results showed that with an increasing Sn content, the band gap of Sn-doped ZnO first decreased and then increased, whereas the band gap of the ZnO base only increased. Sn doping also changed the optical defects of the quantum dots from defects to OZn and Oi defects.